(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Today Digitally empowered India is a scintillating dream of every citizen. “The more technology we infuse in Governance, the better it is for India” these are the words of our Hon’ble Prime Minister who envisions transforming our nation and creating opportunities for all citizens by harnessing digital technologies. His vision is to empower every citizen with access to digital services, knowledge and information. A well connected nation is a rudiment to well served nation. Digital Technologies, which include Cloud computing and Mobile Applications, have emerged as catalysts for rapid economic growth and citizen empowerment across the globe which will have its major impact on the urban and rural areas. Even though many other countries have already progressed in many areas of Digitalization and India has started quite late but I am sure this is going to be worth it and this will be utilized to its maximum potential. Information technology brings a new opportunity-the digital opportunity for the rural population of the country who often suffered by geographical, cultural and linguistic barriers. This will provide them immense possibilities to access information and services. Riding on digital networks Indians are connecting and communicating with each other through mobile phones and computers .This study shall discuss how Digital India is going to revolutionize the way India connects, examining 9 main pillars of Digital India, its projects, estimated cost and impact, role of IOT (Internet of Things, usage of IT in deliverance of services related to various domains such as health, education, agriculture etc., Reducing paperwork with innovative ideas, role of Bharat Broadband Network Limited (BBNL), Ratan Tata’s views on Digital India, contribution by Facebook, Google, Microsoft, Qualcomm and vision of Digital India that every household, every individual should be digitally empowered.